Preparation and Photocatalytic Performance of Cu2O Nanopowders Using Liquid Phase Method - Xu, Ling; Liu, Chang-Ling; Wu, Shi-Biao; Xu, Hai-yan; Zhu, Shao-feng; Feng-Wang; Yang, Li-li; Jia, Guang-Jiu; Li, Jun (Asian Journal of Chemistry, 2013)
Cu2O nanopowders were prepared by liquid phase reduction method by which CuSO4 and Na2SO3 were used as raw materials and the preparation solution pH value was adjusted by NaOH. The nanopowders were charactered by XRD and SEM. According to the XRD results, the nanopowders prove to be Cu2O. The SEM results show that powders were of uniform morphology. The main factors that effect on nanoparticle size of Cu2O were followings: pH, raw materials concentration and reaction time. The Cu2O nanopowders were used as photocatalyst to degrade methyl orange in water solution when photodegradation experiments were carried out. According to the results of photodegradation, the dosage of Cu2O powders, the pH value of methyl orange solution were of obvious effect on photocatalysis efficiency.